Cell-free cloning using multiply-primed rolling circle amplification with modified RNA primers. (July 2009) - Takahashi, Hirokazu; Yamamoto, Kimiko; Ohtani, Toshio; Sugiyama, Shigeru
The predominant method for DNA cloning is by propagation in biological hosts, but this method has limitations because certain sequences are difficult to clone using any combination of available hosts or vectors. Recently, multiply-primed rolling circle amplification (MPRCA) has been applied to overcome the problems of the DNA cloning via host cells. However, when MPRCA is used to amplify from minute quantities of DNA template, the products are mostly by-product DNA molecules generated by false priming and primer dimer formation. This study demonstrates that MPRCA using random RNA primers—instead of DNA primers—blocked the synthesis of by-products and succeeded in amplifying one copy of a circular DNA molecule more than 10 12 -fold to give microgram quantities of amplification product without using submicroliter reaction volumes. Furthermore, a ligation strategy was elaborated to circularize only the desired DNA sequence and eliminate undesired ligation-products. A combination of these methods was able to amplify and ligate a large construct without undesired DNA sequences and at microgram quantities within one day. Therefore, these methods have the possibility to improve DNA cloning techniques that have been restricted by the limitations of PCR methods or by the host cell.